한국잔디 재배에 규산질 비료 시비가 생육과 질소이용효율에 미치는 영향 - 한정지(Jeong-Ji Han); 이광수(Kwang-Soo Lee); 박용배(Yong-Bae Park); 배은지(Eun-Ji Bae) (Weed & turfgrass science, 2014)
This study was conducted to investigate the effect of silicate mixed with nitrogen fertilizer on improving the growth and reducing nitrogen input of zoysiagrass. Plant height, fresh and dry weight of shoots, roots, and stolons, the number of shoots and total of stolons length were increased with highest in silicate mixed with nitrogen 24 kg/10a than nitrogen 24 kg/10a, and it showed no significance in silicate mixed with nitrogen 18 kg/10a. Nitrogen use efficiency in mixed silicate fertilizer was increased by 25-30% than single nitrogen fertilization. Moreover, the contents of available $SiO_2$, and organic matters of silicate fertilization on soil was higher than not silicate fertilization on soil. The silicate enhanced the growth and density of zoysiagrass, while it was a crucial factor to affect the chemical property of the soil. 본 연구는 규산질 비료와 질소 비료 혼용이 한국잔디의 생육과 질소비료 효율에 미치는 영향을 알아보기 위해 수행하였다. 한국잔디의 초장, 지상부, 포복경과 지하부의 생체중과 건물중, 지상부 개체수, 포복경 길이는 규산질 비료 400 kg/10a와 질소비료 24 kg/10a을 혼합시비 하였을 때 질소비료의 24 kg/10a 단용처리구보다 증가하였고, 규산질 비료와 질소비료 18 kg/10a은 질소비료의 24 kg/10a 단용 처리구와 유의성이 없었다. 규산질 비료와 질소비료를 혼합하여 시비했을 경우 질소비료 약 25-30% 절감효과가 있는 것으로 판단되었으며, 토양 내 유효 규산과 유기물의 함량은 규산질 비료 시비를 하지 않은 것보다 시비를 하였을 때 더 높게 나타나 규산질 비료가 한국잔디의 생장과 밀도를 높였으며 토양의 화학적 특성에 중요한 요소로 작용하였다.